The impact of COVID-19 on the mental health of athletes - Personeni, O. (2020)
This retrospective study proposes to understand how social distancing, lockdown, and inability to train and compete are affecting athletes. Existing literature focuses on a series of effects, namely uncertainty about the future, financial instability, and inability to find mental support that are recognized as triggers for anxiety, frustration, anger, depression, and other psychological disorders. This study aims to understand the immediate effects during the lockdown and when athletic activities resumed, by surveying the athletic community at LMU. Through a survey to a group of student-athletes in different disciplines, the study also aims to classify mental distress impacts in team-sports versus individual sports, namely soccer, volleyball and water-polo versus tennis and golf, also differentiating by women and men over a period of roughly nine months. Expected results include for athletes in team sports to experience a more significant deterioration regarding their mental health during lockdown as well as a greater improvement in their mental health when training has resumed; lastly, female athletes are forecasted to be more affected than male athletes during the lockdown.